Game – Philosophy of Child’s Creation and Life - Juodaitytė, Audronė; Malinauskienė, Daiva; Šiaučiulienė, Rūta (Pedagogika, 2015)
The article revealed the game as a social and cultural child’s life and creative philosophical meaningfulness. Scientific discussion and debate problem directions are demonstrated, described their content. Disclosed: what game questions are highlighted in Lithuanian and foreign scientists’ research works in search of his creative, existential, cognitive meanings; why scientists describe the game as a child’s living world project, say that in the scientific meanings, this question is very paradoxical? The paradox interpreted as follows: the more delves into the meanings, the more questions remain unanswered. Issue of the scientific debate and discussion convergent: social, cultural, cognitive, creative meaningfulness of the game to a child’s life. The game features a variety of concepts and the child’s motivation for resolution in the game, the pedagogical conditions of the game, social – philosophical meaningfulness, and effective process of the game, adult’s role in it, the child’s sociocultural competence and expression in adult and children’s cultural possibilities /impossibilities.